The evolution of coil-less inductive behaviour in La-doped Sr2MnO4 - Nirala G.; Katheriya T.; Yadav D.; Verma H.; Upadhyay S. (My University, 2025)
The powder and ceramics of La-substituted layered oxides La xSr2−xMn1−xO4 (x = 0.3, 0.5, 0.7) were synthesised using the solid-state reaction technique. All synthesised compositions have tetragonal structures with space groups I4/mm that are identical to Sr2MnO4, as shown by the Rietveld refinement. XPS spectroscopy demonstrated that Mn exists in the mixed-valence forms Mn3+& Mn4+. Studies of the relationship between AC conductivity and permittivity in response to temperature (30–300°C) and frequency (1 kHz–2 MHz) have demonstrated the existence of negative permittivity over the whole test range. The observed negative permittivity is a result of free carriers oscillating plasmonically between 1 kHz and 2 MHz as a consequence of thermal excitation processes. The modelling of impedance data using various combinations of resistors and inductors exhibited the coil-less inductive characteristics of the samples. The inductive nature of samples indicates the possibility of designing synthesised compositions as coil-less inductors. © 2023, Qatar University and Springer Nature Switzerland AG.